النبات في المغرب الأوسط خلال العصر الوسيط بين الممارسات الطبية والطقوس السحرية. - بن يحى, حبيبة (My University, 2023)
ملخص نظرا لكون النباتات من العناصر الطبيعية، التي تمكن الحياة فوق كوكب الأرض واستمرارها، وقد حاول الإنسان استغلالها في شتى مجالات حياته، فمن مجرد غذاء إلى صناعة ودواء، حيث وصل به الأمر إلى استخدامها في خلطات سحرية، محاولة منه قضاء ما عجز عنه، وكان خارج طاقته في مجالات معينة، وقد حاولنا في موضوعنا هذا ابراز بعض جوانب استخدام النبات في المغرب الأوسط من الجانب الطبي والممارسات السحرية وذكر أهم النباتات المستخدمة لهذا الغرض وبعض طبقات المجتمع التي مارست التطبيب لعلاج أمراض معينة بنوع محدد من النباتات، والاغراض السحرية التي استعملت فيه نباتات ذات خواص معينة. :Abstract Due to the fact that blants are Natural elements that enable life on the blanet and its continuity, and man has tried to exploit them in various aspects of his life, from mere food to industry and medicine, as he came to use them in magical mixtures, trying to spend what he was unable to do, and he was outside lts energy is en certain areas, and we gave tried in this topic to highlight some aspects of the use of plants in the middle Maghreb from the medical side and magical practices and mentioned the most important plants used for this purpose and some layers of society that practiced medicine to treat certain diseases with a specific type of plants, and the magical purposes in which plants of special interest were used certain properties
مقال
Keywords: المغرب الأ ; سط ; العصر ال ; سيط ; النباتات الطبية ; التسحير ; الطق ; س